Perceived risk as a mediator between the behavioural factors and reinvestment intention among millennial retail investors / Maily Patrick - Patrick, Maily (2021)
The millennial cohort is the largest in Malaysia, and this cohort has started to enter the workplace, replacing the baby boomers generation. They are the next generation who will be thinking about where to invest their hard-earned salary. Realising this phenomenon, the Securities Commission has begun to focus on this market segment to encourage millennials‘ direct involvement to invest in stock since 2016. However, the financial market‘s uncertainty and instability due to economic conditions have psychologically and emotionally influenced retail investors, including millennials. Due to millennials‘ unique demographics and characteristics, factors that will entice them to reinvest in the stock market will also be different. Therefore, this research examines the behavioural factors affecting Malaysian millennial retail investors‘ intention to reinvest in the stock market. This study also examines if the perceived risk on stocks could mediate the relationship between the behavioural factors and intention to reinvest in the Malaysian stock market. The social learning theory and the behavioural finance theory; heuristic theory, herding theory, and prospect theory had integrated with an attempt to predict the reinvestment intention of millennial retail investors in the Malaysian stock market. Therefore, the behavioural factors are cognitive, self-efficacy, herding effect and market factors. A primary data collection method via a survey was developed to answer the research questions established. The unit analysis is individual, and there were 258 questionnaires valid for analysis. The structural equation modelling had pursued and variance-based technique exercised; thus, the analysis employed partial least square structural equation modelling (PLS-SEM). The main findings revealed that socio-economic factors (herding effect and market) significantly influenced the millennial retail investors‘ reinvestment intention on the Malaysian stock market. Unfortunately, personal factors (cognitive and self-efficacy) do not significantly influence millennial retail investors‘ reinvestment intention on stocks. The key findings highlight that the perceived risk partially mediate the relationship between the herding effect and reinvestment intention in the Malaysian stock market among millennial retail investors. The arguments have linked to the risk attitudes of retail investors, particularly the risk-averse and risk-seekers attitudes and regret aversion. Therefore, the findings indicate that the data support the prospect theory and herding theory. Indeed, the findings contribute to the body of knowledge and managerial aspects, particularly to the authorities, financial institutions, publicly listed companies, professional financial advisors, remisiers, dealers, and retail investors.